The Influence of Digital Mobile Learning on Science Learning Outcomes on Theme 2 Clean Air on the Health of an Elementary School Students During the Pandemic Period: ʻPengaruh Pembelajaran Digital Mobile Learning Terhadap Hasil Belajar IPA pada Tema 2 Udara Bersih Bagi Kesehatan Siswa SD Di Masa Pandemi - Ananda Firdaus; Enik Setiyawati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine whether there is an effect of Digital Mobile Learning on Science Learning Outcomes on Theme 2 Clean Air on the Health of Muhammadiyah 9 Ngaban elementary students during the Pandemic Period. The type of this research is quantitative experiment with pre-experimental designs in the form of one-group pretest-posttest design. The instrument in this study used a test instrument. While the subjects in this study were fifth grade students. The results of the study show that there is an influence of digital mobile learning on science learning outcomes. The results of the calculation of the normality test 3.67 < 9.488. The next calculation is to test the hypothesis in the results of 4.415 > 2.042, which means that there is a significant difference. The large effect test shows that 0.38 > 0.14 which interprets the existence of a large and large effect of 14.90%.